2022
DOI: 10.1021/jacs.2c02703
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering the Chemical Nature of Strand Breaks Derived from Abasic Sites in Cellular DNA: Evidence for 3′-Glutathionylation

Abstract: The hydrolytic loss of coding bases from cellular DNA is a common and unavoidable reaction. The resulting abasic sites can undergo β-elimination of the 3′-phosphoryl group to generate a strand break with an electrophilic α,β-unsaturated aldehyde residue on the 3′-terminus. The work reported here provides evidence that the thiol residue of the cellular tripeptide glutathione rapidly adds to the alkenal group on the 3′-terminus of an AP-derived strand break. The resulting glutathionylated adduct is the only majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 137 publications
3
14
0
Order By: Relevance
“…Notably, Yang and colleagues also showed that the half-life of Schiff base DPCs derived from histone and 3′-pUA ranges from 10 to 14 h in vitro ( 49 ). Overall, our observations of the important role of GSH in forming GSH-adducted SSB and in competing with TFAM in the DPC formation corroborate results from the Gates and Wang laboratories showing the glutathionylation of β-elimination products of AP sites in nDNA ( 30 , 50 ). Additional studies are needed to clarify which type(s) of TFAM-induced DNA modifications are more persistent in vivo .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Notably, Yang and colleagues also showed that the half-life of Schiff base DPCs derived from histone and 3′-pUA ranges from 10 to 14 h in vitro ( 49 ). Overall, our observations of the important role of GSH in forming GSH-adducted SSB and in competing with TFAM in the DPC formation corroborate results from the Gates and Wang laboratories showing the glutathionylation of β-elimination products of AP sites in nDNA ( 30 , 50 ). Additional studies are needed to clarify which type(s) of TFAM-induced DNA modifications are more persistent in vivo .…”
Section: Discussionsupporting
confidence: 89%
“…We verified the formation of a reactive 3′-phospho-α,β-unsaturated aldehyde residue (3′pUA, shown in Figure 2A ) by comparing products with those from well-characterized reactions from NaOH or DNA glycosylase-catalyzed reactions ( 28 ), or by trapping with thiol-containing chemicals, such as β-mercaptoethanol (βMe) or GSH. Small molecule thiols ( 29 , 30 ) or Cys residues ( 31 ) are known to be able to conjugate with an α,β-unsaturated aldehyde via 1,4-addition. As shown in Figure 2B (lanes 2, 3, 14, and 15), reactions with AP(5′) under mild and strong NaOH treatment proceeded primarily via β-elimination and β,δ-elimination, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the Gates and Guengerich laboratories have independently described thiol adducts formed at abasic sites and abasic site-derived cleavage products. In Figure , we present a structure consistent with the observed mass, although other structural isomers are possible. Interestingly, we find that the PUA is reactive with a broad range of nucleophiles.…”
Section: Resultssupporting
confidence: 80%
“…Mammalian AP-endonuclease APE1 was shown to be capable of removing the 3′-PUA generated from the β-elimination of the AP site. , APE1 may also trim GS-ddR to produce a 3′-hydroxyl terminus for polymerase β-mediated gap filling, and the endonuclease activity of APE1 on AP sites precludes the generation of GS-ddR. We used the APE1 inhibitor CRT0044867 to examine the influence of APE1 inhibition on the generation of GS-ddR.…”
Section: Resultsmentioning
confidence: 99%
“…3′-PUA exhibits high reactivity with thiol, and we recently reported the formation of the 3′-glutathionylated DNA strand-cleavage product, that is, 3′-glutathionyl-2,3-dideoxyribose (GS-ddR), in synthetic duplex DNA in vitro (Scheme ). Considering that the cellular concentration of GSH ranges from 0.5 to 10 mM, , we reason that the same product may form in cellular DNA. Here, we developed a stable-isotope-dilution-based liquid chromatography tandem mass spectroscopy (LC–MS/MS) method for the quantification of the basal level and MNU-induced formation of GS-ddR in cultured human cells.…”
Section: Introductionmentioning
confidence: 99%